2017
DOI: 10.1039/c7ra01902e
|View full text |Cite
|
Sign up to set email alerts
|

Indenothiophene-based asymmetric small molecules for organic solar cells

Abstract: The development of organic semiconductors is of key importance in order to improve the performance of organic solar cells (OSCs). Three indenothiophene (IT)-containing small molecules (IT3T, ITFBT and IT2FBT)were designed and synthesized for small molecule OSCs. The thermal, optical, and electrochemical properties of the molecules were investigated. The optical bandgaps of the three small molecules are ranged from 1.80 to 2.20 eV depending on different terminal groups flanked on the IT. We study the photovolta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…These results suggested that both the SMs had good thermal stability. Compared with IT2FBT ( T d : 398 °C) [29] , IT(2FBT-T3Cz) 2 and IT(2FBT-TT3Cz) 2 presented higher T d . Therefore, incorporating the 3-carbozol terminal groups could improve the thermal stabilities of its resultant compounds.…”
Section: Thermal Propertiesmentioning
confidence: 83%
See 1 more Smart Citation
“…These results suggested that both the SMs had good thermal stability. Compared with IT2FBT ( T d : 398 °C) [29] , IT(2FBT-T3Cz) 2 and IT(2FBT-TT3Cz) 2 presented higher T d . Therefore, incorporating the 3-carbozol terminal groups could improve the thermal stabilities of its resultant compounds.…”
Section: Thermal Propertiesmentioning
confidence: 83%
“…The results demonstrated that the asymmetric indenothiophene can be an excellent donor core for organic semiconductors. Then Zheng's group also introduced IT to construct SMs donor materials for OSCs [29] . However, the maximum PCE of asymmetric IT-based device was only 4.57%.…”
Section: Introductionmentioning
confidence: 99%
“…Huang et al reported four asymmetric molecules with varying terminal units and found that the increase in the donor-to-PC 71 BM dipolarity difference adversely influenced the donor-to-PC 71 BM phase-separation. 17 Besides this, asymmetric small molecules based on the building blocks diketopyrrolopyrrole, 23 benzothiadiazole, 24 indenothiophene, 18,25 squaraine, 26,27 and triphenylamine 28 have been reported for use in OSCs.…”
Section: Introductionmentioning
confidence: 99%